Peranan Etika Bisnis Dalam Tantangan Strategi Bisnis Di CV. Inti Motor - Ibnu Khoirudin; Fathan Ahlul Haq; Ananda Nur Wahit; Elsa Nur Safitri; Nur Sahid Gatot Nugroho; Aris Prio Agus Santoso (Pusat Riset dan Inovasi Nasional, 2024)
Business ethics play an important role in creating and maintaining a healthy work culture in a company. CV. Inti Motor is a company that operates to challenge business strategies based on the principles of business ethics. This research discusses how the application of business ethics principles can influence a company's internal dynamics. Research was conducted through literature analysis and direct observation. Research shows that business ethics have become the basis for internal policies, decision making, and management-employee relations. The researcher took the first important point, namely justice, ethics and good business strategies in maintaining the work environment. Considering that the marketing division has tighter competition between sales, so that some business ethics are not paid attention to, which causes frequent conflicts in the work environment. The results of this research show that ethical business practices are very important to maintain a fair, inclusive and productive work environment, before embarking on business strategy challenges that will ultimately support the company's long-term success.